Sites of insight: a guide to Colorado sacred places - Lough, James, editor; Smith, Christie, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2003)
In these eighteen illuminating essays, some of Colorado's most accomplished novelists, essayists, and poets write in intimate detail about their most poignant experiences in the Colorado wilderness. Readers are given access - both physically and spiritually - to settings that inspire reverence for and contemplation about one's relationship to the land. From above tree line in the Rawah Mountains down into the broad San Luis Valley, from the Western Slope to the high plains in the east, the reader is taken on a journey through a assortment of Colorado's landscapes.--Book jacket.
Keywords: Sacred space -- Colorado; Colorado -- Religion